Older Patients Undergoing Bipolar Hemiarthroplasty Face a Higher Risk of Intraoperative Fractures and Longer Hospital Stays on Delayed Surgery After Injury - Hirotaka Kawakami, MD, PhD; Hiromi Sasaki, MD, PhD; Junichi Kamizono, MD, PhD; Hiroaki Sawazono, MD; Yoshitaka Yamashita, MD; Yusuke Fujimoto, MD, PhD; Noboru Taniguchi, MD, PhD (JBJS Open Access, 2025)
Background:. Intraoperative fractures are a significant complication of bipolar hemiarthroplasty for hip fractures in older patients. Femoral geometry classified as Dorr C is associated with a high risk of intraoperative fractures when a cementless stem is used. However, the impact of the duration from injury to surgery on the risk of intraoperative fractures remains unclear. We hypothesized that a prolonged duration from injury to surgery increases the likelihood of intraoperative fractures. The aim of this study was to evaluate the relationship between the duration from injury to surgery and the occurrence of intraoperative fractures. Methods:. This case-control study analyzed 548 patients who underwent bipolar hemiarthroplasty for hip fractures at 2 hospitals between April 2017 and March 2024. The patients were categorized into 2 groups based on the occurrence of intraoperative fractures: the “intraoperative fracture (+) group” and “intraoperative fracture (−) group.” The relationship between intraoperative fractures and the duration from injury to surgery was assessed. Results:. Intraoperative fractures occurred in 37 of 548 cases. The duration from injury to surgery was 6.05 and 3.56 days in the intraoperative fracture (+) and (−) groups, respectively (p = 0.002). The canal flare index (CFI) was 3.30 and 3.73 in the intraoperative fracture (+) and (−) groups, respectively (p < 0.001). Logistic regression analysis revealed that the regression coefficient for the duration from injury to surgery was 0.04 (p = 0.04), and for CFI −1.09 (p < 0.001), both associated with an increased risk of intraoperative fracture. In patients with intraoperative fractures, an investigation into delays in surgery beyond 48 hours showed that more than half of these delays were due to hospital-related concerns. Conclusions:. Intraoperative fractures increase with the CFI and duration from injury to surgery. In some cases, medical facilities may be able to reduce this duration. To minimize the risk of intraoperative fractures in bipolar hemiarthroplasty for older patients, reduction of the duration from injury to surgery is essential. Level of Evidence:. Level III, Case-control study. See Instructions for Authors for a complete description of levels of evidence.